Isolation of anticancer and antimicrobial metabolites from Epicoccum nigrum; endophyte of Ferula sumbul. (September 2017) - Perveen, Irum; Raza, Muhammad Asam; Iqbal, Tahir; Naz, Iffat; Sehar, Shama; Ahmed, Safia
Abstract: Owing to the importance of endophytes, current research was aimed to purify the secondary metabolites from targeted source. Ferula sumbul, a lipophilic extract of the endophyte was prepared in 10% methanol and partitioned with ethyl acetate and bioassay guided isolation was carried using standard protocols against bacterial, fungal and cancer cells. The active fractions consisted of three new metabolites (2-methyl-3-nonyl prodiginine, Bis (2-ethylhexyl) phthalate, and a meroterpenoid, Preaustinoid A). Their structures were confirmed with LCMS/MS. The purified metabolites showed valuable results against tested activities which concluded that these compounds have great potential and these may be applicable to textile (dyeing), pharmaceutical (drug, infectious agents) and food (preservatives) industries. This study reveals the potential of E. nigrum as an important source of bioactive compounds including 2-methyl-3-nonyl prodiginine, Bis (2-ethylhexyl) phthalate, and Preaustinoid A. This is first report of isolation of prodiginines as well as meroterpenoid and Bis (2-ethylhexyl) phthalate from Epicoccum nigrum .